Optimization of the Centrifugal Spinning Parameters to Prepare Poly(butylene succinate) Nanofibers Mats for Aerosol Filter Applications - Ayben Pakolpakçıl; Ali Kılıç; Zbigniew Draczynski (Nanomaterials, 2023)
Air pollution is becoming a serious issue because it negatively impacts the quality of life. One of the first most useful self-defense approaches against air pollution are face masks. Typically made of non-renewable petroleum-based polymers, these masks are harmful to the environment, and they are mostly disposable. Poly(butylene succinate) (PBS) is regarded as one of the most promising materials because of its exceptional processability and regulated biodegradability in a range of applications. In this regard, nanofiber-based face masks are becoming more and more popular because of their small pores, light weight, and excellent filtration capabilities. Centrifugal spinning (CS) provides an alternative method for producing nanofibers from various materials at high speeds and low costs. This current study aimed to investigate the effect of processing parameters on the resultant PBS fiber morphology. Following that, the usability of PBS nonwoven as a filter media was investigated. The effects of solution concentration, rotating speed, and needle size have been examined using a three-factorial Box–Behnken experimental design. The results revealed that PBS concentration had a substantial influence on fiber diameter, with a minimum fiber diameter of 172 nm attained under optimum production conditions compared to the anticipated values of 166 nm. It has been demonstrated that the desired function and the Box–Behnken design are useful instruments for predicting the process parameters involved in the production of PBS nanofibers. PBS filters can achieve an excellent efficiency of more than 98% with a pressure drop of 238 Pa at a flow rate of 85 L/min. The disposable PBS filter media was able to return to nature after use via hydrolysis processes. The speed and cost-effectiveness of the CS process, as well as the environmentally benign characteristics of the PBS polymer, may all contribute considerably to the development of new-age filters.